The clinical course of hypertrophic cardiomyopathy and the role of polymorphisms in the intronic and promoter regions of the gene alpha-galactosidase A - A. A. Poliakova; E. N. Semernin; A. Ya. Gudkova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The article reflects the importance of timely diagnosis sarcomeric and non sarcomeric hypertrophic cardiomyopathy (HCM). The results of the phenotypic and genotypic screenings aimed at identifying HCM phenocopies and, in particular Fabry disease, in the structure of left ventricular hypertrophy of unknown origin in patients of the North-West region of Russia. We analyzed the influence of polymorphisms in the intronic and promoter regions of the GLA gene on clinical course and the presence of extracardiac manifestations.